A low-cost IoT-based auscultation training device - Heri Andrianto Andrianto; Daniel Perdana Sutanto; Yunus Adhy Prasetyo (Institute of Advanced Engineering and Science, 2021)
Auscultation training devices are needed by teachers and students in health schools to practice auscultation techniques. In this paper, a low-cost IoT-based auscultation training device has been developed using NodeMCU, four proximity sensors, metal as a stethoscope, a switch, an android smartphone, an earphone, and a phantom doll. The message queuing telemetry transport (MQTT) protocol has been used for data communication between NodeMCU and smartphones, therefore an auscultation training hardware can be used by many students who have auscultation training application on their smartphones that subscribe to topics. The results showed that an auscultation training device was able to detect a stethoscope. Auscultation training application on a smartphone successfully plays normal and abnormal breathing sounds based on subscribed topics. With a production cost of less than 15 USD, we offer an inexpensive IoT-based auscultation training device.